ASSESSING EXPERIENCE, EDUCATION, PROFESSIONAL SKEPTICISM AUDITORS IN DETECTING FRAUD - Vero Deswanto (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2020)
Fraud is an act of fraud with a mechanism of action that is planned and carried out individually, in groups or in collaboration with other parties. The auditor profession is responsible for fraud detection. Increased emphasis on the grading system is needed in connection with detection. This research was conducted at the Inspectorate General of the Ministry of Finance by conducting a survey of 82 auditors. The data analysis technique used is multiple linear regression analysis that is processed using the Smart-PLS tool. Hypothesis testing results show that experience, education, and professional skepticism have a positive effect on auditor perceptions in detecting fraud. Test results and statistical data analysis concluded that the auditor's experience showed a positive effect on the auditor's perception in detecting fraud even though it was not significant, the auditor's education variable showed a positive and significant effect on the auditor's perception in detecting fraud, and the professional skeptic variable had a positive effect on the auditor's perception in detecting cheating and its influence is significant.